If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying dx + g = 0 Solving dx + g = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1g' to each side of the equation. dx + g + -1g = 0 + -1g Combine like terms: g + -1g = 0 dx + 0 = 0 + -1g dx = 0 + -1g Remove the zero: dx = -1g Divide each side by 'x'. d = -1gx-1 Simplifying d = -1gx-1
| 3x+-2y=zfory | | 3r=-45 | | -0.6+0.5x+4=5 | | 5(x+2)+4x=55 | | 2m-9m=12 | | 3m^2-18=0 | | 25(b+826)-804=-29 | | P=120-0.03x | | 3r+11s= | | 5N(-8+4T)= | | 3(w-93)+99=24 | | Y=lnex^2-1 | | 0.16(y-7)+0.18y=0.14y-0.05(10) | | 6x-4+4x+17-9x=34 | | 6w+z-5w-z= | | 3(n-4)=3 | | 15+(2+x)=(15+2)+x | | 14.5=3.4(z-12.8)-2.5 | | 3+4(2x-3)-5x=16+5 | | 10p^2-8p-14=0 | | Cos(x)=y | | 4z-10-9z= | | -4/7y=32 | | -2.36(g+3)=0 | | 2x-4-6x+1= | | -9c-2=-(-5c+2)+4(3-5c) | | 2.8-z=1.08 | | (3u-27)(u^2+6u-7)=0 | | 9=6x-5x+2 | | h+9.7=9.7 | | 4x-32=5x-25 | | .7(x+60)+.9x=106 |